Fishing Vocabulary in Russian Subdialects on the Territory of the Republicof Mordovia - Elvira N. Akimova; Tatiana I. Mochalova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The paper concerns the linguistic units that nominate objects, actions, concepts related to the process of fishing in Russian folk dialects that exist on the territory of Mordovia. The specificity of nominative processes associated with the fixation of a linguistically significant fact in the language is determined. The study is conducted on the material of the Dictionary of Russian subdialects in the territory of the Republic of Mordovia. It has been established that two main groups of names are actively used in Russian dialects: ichthyonyms, or different types of fish; various devices used for fishing. The largest group consists of ichthyonyms that name fish species. They show region fauna variability of aquatic representatives, point out the factors, which constitute the basis for their nomination, reveal the features of fish that are important in the dialect community. It has been determined that among the recorded numerous names of various fishing tackle used by a person in the process of fishing, fishing nets are the most diverse in the Russian dialects of Mordovia. The study has shown that different types of dialectisms can be distinguished in the composition of the fishing vocabulary, namely: the most common are proper lexical dialectisms, the roots of which have no correspondences in the national language, national words that have different meanings in a dialect system, referred to as lexico-semantic dialectisms, are also actively used. Most of the described words are unambiguous, but there are also solitary polysemantic lexemes. Derived meanings of a word in a dialect environment appear, as a rule, on the basis of an anthropomorphic or material metaphor.